2020
DOI: 10.1177/0731684420901754
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the quasi-static and dynamic piezoresistive behavior of multi-walled carbon nanotubes/elastomer composites

Abstract: Multi-walled carbon nanotube (MWCNT)/elastomer composites exhibit a piezoresistive behavior, i.e. their resistivity changes when they are subjected to mechanical loading. Thus, these materials can be used as strain or pressure sensors. In this paper, the effect of carbon nanotube weight fraction on the sensitivity and repeatability of the electrical response of multi-walled carbon nanotube/ethylene–propylene–diene monomer composites is investigated, under quasi-static and dynamic compression (using split Hopki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…An electrical current I in the range of 10 µA to 3 mA was input through a linear measurement device. Thanks to this electronic scheme (see [39]) the range of measurement can be adapted by choosing an appropriate input current value. This setup gives the electrical voltage V as output, which in turn is used to calculate the electrical impedance at the macro-scale Z = V /I.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An electrical current I in the range of 10 µA to 3 mA was input through a linear measurement device. Thanks to this electronic scheme (see [39]) the range of measurement can be adapted by choosing an appropriate input current value. This setup gives the electrical voltage V as output, which in turn is used to calculate the electrical impedance at the macro-scale Z = V /I.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The Ogden hyper-elastic constitutive model was used. The experimental engineering stress-strain curve σ (ε) (ε is the change in length to original length ratio) was provided by [39]. This enables to determine the material constants µ m and α m .…”
Section: Constitutive Lawmentioning
confidence: 99%
“…In 2007, Bokobza 47 reported that the addition of carbon black (CB) particles may improve the formation of connected networks in elastomeric-based composites reinforced with carbon nanotubes, by bridging isolated nanotubes. 47,165 More recently, Penvern et al 166 manufactured EPDM composites reinforced with both CB and MWCNTs. They also confirmed that carbon black particles act as bonding agents between MWCNTs and the elastomeric macromolecules, which helps obtain homogeneous filler dispersion inside the matrix.…”
Section: Effect Of the Addition Of A Second Fillermentioning
confidence: 99%